Sistem Perizinan Santri Berbasis Web dengan Fitur Whatsapp Menggunakan Framework Laravel (Studi Kasus pada Pondok Pesantren Luhur Wahid Hasyim Semarang Putri) - Zuhrof Karima Hamidah; Arief Hidayat (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
Luhur Wahid Hasyim Islamic Boarding School is one of the huts located in the Semarang area, to be precise, in the Sampangan Village. The Islamic boarding school is part of the Wahid Hasyim Semarang University (UNWAHAS) foundation. In implementing the student licensing system, Luhur Wahid Hasyim Islamic Boarding School still applies the conventional system, students must meet the management and fill in the data in the permit book when applying for a permit. The licensing process using this method raises problems such as the large number of students who do not carry out permits according to the procedure, the data of students whose permits cannot be managed validly due to negligence. The purpose of this research is to produce a system that can speed up the process of managing, inputting, and storing student licensing data more effectively and efficiently. In making this information system the author uses the waterfall method which is the development of a system or software with the process of working on a system carried out sequentially and systematically. The results of this study are a web-based licensing system at the Luhur Wahid Hasyim Islamic Boarding School using the Laravel Framework. This licensing system can assist students in applying for permits at PPLWH more effectively and efficiently, assisting administrators in viewing lists of permit applications and recapitulating permits according to the type.